MUC1 aptamer-tethered H40-TEPA-PEG nanoconjugates for targeted siRNA-delivery and gene silencing in breast cancer cells - Salve, Rajesh; Haldar, Niladri; Shaikh, Aazam; Samanta, Rajkumar; Sengar, Devyani; Patra, Surajit; Gajbhiye, Virendra (Frontiers in Bioengineering and Biotechnology, 2024)
With a prevalence of 12.5% of all new cancer cases annually, breast cancer stands as the most common form of cancer worldwide. The current therapies utilized for breast cancer are constrained and ineffective in addressing the condition. siRNA-based gene silencing is a promising method for treating breast cancer. We have developed an aptamer-conjugated dendritic multilayered nanoconjugate to treat breast cancer. Initially, we transformed the hydroxyl groups of the hyperbranched bis-MPA polyester dendrimer into carboxylic groups. Subsequently, we linked these carboxylic groups to tetraethylenepentamine to form a positively charged dendrimer. In addition, the mucin-1 (MUC1) aptamer was attached to the dendrimer using a heterobifunctional polyethylene glycol. Characterizing dendrimers involved 1H NMR and dynamic light scattering techniques at every production stage. A gel retardation experiment was conducted to evaluate the successful binding of siRNA with targeted and non-targeted dendrimers. The targeted dendrimers exhibited no harmful effects on the NIH-3T3 fibroblast cells and RBCs, indicating their biocompatible characteristics. Confocal microscopy demonstrated significant higher uptake of targeted dendrimers than non-targeted dendrimers in MCF-7 breast cancer cells. The real-time PCR results demonstrated that the targeted dendrimers exhibited the most pronounced inhibition of the target gene expression compared to the non-targeted dendrimers and lipofectamine-2000. The caspase activation study confirmed the functional effect of survivin silencing by dendrimer, which led to the induction of apoptosis in breast cancer cells. The findings indicated that Mucin-1 targeted hyperbranched bis-MPA polyester dendrimer carrying siRNA could successfully suppress the expression of the target gene in breast cancer cells.